Batalha contra Gaudério: Representações das masculinidades infantis nos primeiros anos de publicações da revista “O Tico-Tico” (1905 – 1906) - Silva, Carlos Gabriel Ferreira da (2020)
"O Tico-Tico" is considered by historiography one of the first brazilian magazines for children. It was created in 1905 by Sociedade Anônimo O Malho, headed by Luíz Bartolomeu de Souza with the purpose of entertaining, recreating and also assisting in the process of transforming brazilian children into healthy and upright citizens. O Tico-Tico emerged within a feeling of renewal from several brazilian intelectual groups that the country was overdue, diseased and unlettered. When children's journalism started to rise, O Jornal das Crianças opened doors to great illustrators and writers. This report introduces the porposal of a thematic catalog “Batalha contra Gaudério” (“Battle against Gaudério”, in english), which analyzes and realy about boys representations about work, punishment and body from 1905 and 1906. Therefore, we used Social History of The Press and Cultura History Representations theories, and also build on the Philippe Ariès theses’ (Family and awareness of infancy) and Joan Scott’s (gender).